De Recrutering Van De Jezuïeten in Het Hertogdom Brabant (1584-1640): Recruitment by the Jesuits in the duchy of Brabant, 1584-1640. - Labbeke, Liesbeth (Trajecta, 1996)
Examines the growth in the recruitment of novices by the Jesuits in the southern Netherlands in the early 17th century, focusing on candidates born in Brabant. As time went on, the candidates tended to be younger and less educated than they were at the end of the 16th century.